The effects of heatwaves on hospital admissions in the Edirne province of Turkey: A cohort study - (:unkn) unknown (My University, 2023)
Studies show that heat waves (HWs) are among the most important atmospheric phenomena that negatively affect human health. This study aims to determine the effects of HWs on hospital admissions (HA) in the Edirne province of Turkey. Polyclinic admission and atmospheric data, including daily maximum temperatures, were used. HW is defined as temperature at the % 90 threshold of daily maximum temperatures that persists for at least 3 consecutive days or more. With this definition, a 6-day HW was detected, and a lag of 3 days was added to this HW. Logarithmic Z test was used for the analysis. As a result of the study, The Risk Ratio (RR) showing the relationship between 9-day HW and HAs was calculated as 1.19 (95% confident interval [CI]: 1.17-1.21, P < .05), and it was determined that there were 2557 extra HAs in total. When HAs were analyzed according to sex, it was observed that female admissions were higher than male admissions. To analyze admissions by age, the data were divided into 3 groups: children (<15 years), adult (15-64 years), and elderly (≥65 years). As a result of the analysis, the highest increase was observed in patients < 15 years of age, and the RR was 1.33 (95% CI: 1.24-1.42 P < .05). When the patient density in polyclinics was analyzed, the Cardiology polyclinic had the highest number of patient admissions with an RR, 1.36 (95% CI: 1.30-1.43 P < .05). The results of this study will guide measures to be taken against HWs.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine